The Influence of Discipline, Organizational Culture and Work Motivation against Employee Performance at Perum Bulog East Java Regional Office - Nurindah Dwi Antika (Jurnal Akuntansi, Manajemen dan Ekonomi, 2022)
Quality human resources are a determining factor in improving the performance of a business organization. The performance of a business organization is largely determined by the performance of its employees, and this is the main reason for this research. This study aims to determine the effect of discipline, organizational culture and work motivation on employee performance. This research approach is a descriptive research with a quantitative approach. The data used in this study are primary data obtained directly from respondents through questionnaires in the field and secondary data obtained in finished form, has been collected and processed by other parties. The number of samples taken in this study were 74 respondents. The data analysis technique used in this research is multiple linear regression. The results of the analysis show that the variables of discipline, organizational culture and work motivation have a significant effect on employee performance both simultaneously and partially. The results of this study indicate that the variables of discipline, organizational culture and work motivation are the determining variables in an effort to improve employee performance